Effects of isolation damping and stiffness on the seismic behaviour of structures - Abrishambaf, Amin; Özay, Giray (My University, 2010)
As it is known earthquakes uncontrollably occur. As soon as a seismic activity begins, the ground starts to vibrate and thereby and release high amounts of energy, some of which absorbed by the structure. This absorbed energy when exceeds the elastic limit of structure causes inevitable occurrence of damages. From another point of view, increase in the strength of the building is not limitless. Base isolation is another approach, which is different from the above mentioned. It is based on the concept covering the reduction in the seismic demands rather than increasing the earthquake resistance capacity of the structure. With this paper, it is intended to clarify the seismic performance and optimum bearing with respect to the seismic demand of the 3, 6 and 9-storied base isolated structures isolated by lead-rubber bearing, high damping rubber bearing and friction pendulum system, in order to have materials saving. The comparison process has been carried out on seismic performances of the structures with transmitted acceleration, maximum structural displacement and seismic coefficient. Based on the obtained results, it could be inferred that the lead rubber bearing represents minimum transmitted acceleration and seismic coefficient while the friction pendulum system, due to the high friction of coefficient, minimizes displacement.
European Conference of Chemical Engineering, ECCE'10, European Conference of Civil Engineering, ECCIE'10, European Conference of Mechanical Engineering, ECME'10, European Conference of Control, ECC'10 --
Keywords: Base isolation; Damping; Earthquake; Seismic isolator; Strengthening